Design for Environment e Lean Manufacturing: uma relação para o ciclo de desenvolvimento do produto - Pinto Junior, Marcos José Alves (2016)
This research is an exploratory study presenting the Design for Environment - DfE as one of the environmental management practices in Industrial Ecology in the product development cycle. The DfE should examine the entire life cycle of a product, such as its development, manufacture, use and disposal proposing changes to the project in order to minimize its environmental impact. This product design technique makes it possible to achieve the usual goals in their design, such as performance, reliability and cost of manufacturing. These together with environmental goals, for example to reduce environmental damage, reduced use of resources, increasing energy efficiency and material recycling. Thus, there is need for replacement almost obligatory for some product types. However, the rapid replacement of these products, as well as its disposal can create serious environmental problems, by volume, the material in its composition that take a long time to decompose, such as plastic, glass and metal, but especially because of the heavy metals that can compose, are highly damaging to human health. Not being enough, there are still suitable locations for disposal of many products into disuse. The growth of the contingent of consumers who prefer to buy goods and services that respect the nature is one of the factors that drives the treatment of environmental problems, in addition to the rapid popularization of products and obsolescence of some models. Aspects of reduction of natural resources can be developed into a company that include one Lean Manufacturing environment that aims at a reduction of waste, seeking to improve productivity and quality. This relationship contribute to sustainable development suggesting the existence of an enabling environment for the realization of efforts aimed at reducing or eliminating waste. Through a case study it became clear that DfE practices is related to some Lean tools, as part of its purpose. Also some tools that the company uses environmental exert influence, may be applied in product design to minimize the environmental impact. This work presents the practices observed by a Literature Review Systematic comparison with the case study and the DfE practices that relate to Lean.